The Relationship Between Therapeutic Communication And The Anxiety Levels Of Families Of Patients In The Intensive Care Unit - Marissia Leviani Bowonseet Marissia; Mokhtar Jamil (CV. AFDIFAL MAJU BERKAH, 2026)
Families of patients receiving treatment in the Intensive Care Unit (ICU) often experience anxiety due to the patient's critical condition and the uncertainty surrounding the treatment process. This study aimed to analyze the relationship between nurses' therapeutic communication and the anxiety levels of patients' families in the ICU of Kotamobagu Regional General Hospital. The study employed an analytical correlational design with a cross-sectional approach involving 43 respondents selected using a purposive sampling technique. Data were collected using the Therapeutic Communication Questionnaire and the Hamilton Anxiety Rating Scale (HARS), and were analyzed using the Pearson Product Moment correlation test. The results showed that nurses' therapeutic communication was categorized as good, with a mean score of 92.99, while the family anxiety level was categorized as moderate, with a mean score of 47.46. There was a strong and significant negative relationship between nurses' therapeutic communication and family anxiety levels (r = -0.721; p = 0.000), indicating that better therapeutic communication provided by nurses was associated with lower anxiety levels among patients' families in the ICU.